Analysis of the Altman Z-Score and Springate Methods for Predicting Financial Distress at PT Adhi Karya (Persero) TBK for the Period 2019-2024 - Ego Teza Pradika; Widya Intan Sari (Indonesian Economic Review, 2026)
This study aims to analyze the potential level of financial distress at PT Adhi Karya (Persero) Tbk during the period 2019–2024 using two prediction methods, namely Altman Z-Score and Springate. This research also aims to compare the differences in results between the two methods in predicting financial distress conditions. Financial distress is an early stage prior to bankruptcy that may cause significant losses if not properly anticipated. Therefore, an analysis that provides early warning signals regarding a company’s financial condition is required. The research method employed is a descriptive and comparative quantitative approach using secondary data in the form of annual financial statements of PT Adhi Karya (Persero) Tbk obtained from the company’s official website, www.adhi.co.id. The results indicate that based on the Altman Z-Score method, PT Adhi Karya (Persero) Tbk is classified in the grey area, which means the company is in a risky condition but has not yet been categorized as bankrupt. Meanwhile, based on the Springate method, the company is identified as experiencing financial distress. Based on descriptive statistical analysis, the differences in results produced by both methods indicate that no single approach is fully capable of representing the company’s financial condition comprehensively. Each method has its own characteristics and limitations. Therefore, the use of more than one analytical method is necessary to obtain a more comprehensive understanding of the company’s financial health